The Effects of Fixed-Time Ramp Metering on Freeway Traffic Characteristics Using Microscopic Traffic Simulation - Karim, Dr. Hardy Kamal; Majid, Dr. Hirsh Muhamad; Ahmed, Dr. Chro Haidar (Sulaimani Journal for Engineering Sciences, 2018)
The effects of fixed-time ramp metering on the speed, density and flow of traffic in the influence area of freeway-ramp junctions were explored in this paper. The traffic parameters were obtained from the microscopic VerkehrIn Städten – SIMulations Model (VISSIM 5.40) stochastic simulator program. Four hundred models were built to obtain the traffic stream characteristics. Two fixed-time traffic signals for the ramp meters were assumed and applied for two different assumed geometric configurations of ramp-freeway junctions (Type I and Type II). Different traffic volume conditions were assumed for the ramps and the freeways to represent various traffic flow conditions on the downstream of the freeway. The ramp traffic volume was started from 200 vehicles per hour per lane (vphpl) to 1100 vphpl, with an increment of 100 vphpl; while, the traffic volume of the freeway was started from 400 vphpl to 2000 vphpl with an increment of 200 vphpl. Cameras and traffic detectors were installed at two sites of ramp-freeway junctions in the Kansas City metropolitan area to collect traffic data for the calibration process. The following traffic data were collected for the calibration process: the ramp traffic signal times, queue lengths on the ramp, traffic flow and composition of the ramp and freeway, speed of the vehicles at the upstream and downstream of the freeway. The relationship between the speed-flow-density of the vehicles within the ramp influence area with and without using ramp metering was obtained. The results of the study showed that ramp metering has different effects on the traffic flow characteristics based on the geometric configuration of the ramp-freeway junction and traffic flow conditions. Regarding the Type I junction, ramp metering could increase the average speed of the vehicles within the influence area when the flow was greater than 1000 vphpl; the Type II junction, however, did not show significant result. Based on these results, the study recommends that before implementing ramp metering on the ramp, a detailed study should be made of the geometric configuration of the ramp-freeway junction, and of the traffic flow conditions.
Keywords: Ramp meter; Microscopic Simulation; Speed; Flow; Density